2009
DOI: 10.1242/jeb.030817
|View full text |Cite
|
Sign up to set email alerts
|

The role of signalling molecules on actin glutathionylation and protein carbonylation induced by cadmium in haemocytes of musselMytilus galloprovincialis(Lmk)

Abstract: SUMMARYThis study investigated the role of Na + /H + exchanger (NHE) and signalling molecules, such as cAMP, PKC, PI 3-kinase, and immune defence enzymes, NADPH oxidase and nitric oxide synthase, in the induction of protein glutathionylation and carbonylation in cadmium-treated haemocytes of mussel Mytilus galloprovincialis. Glutathionylation was detected by western blot analysis and showed actin as its main target. A significant increase of both actin glutathionylation and protein carbonylation, were observed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 114 publications
1
16
0
Order By: Relevance
“…Our results also indicate that the mechanism of 17b-estradiol-induced adhesion to laminin-1, collagen IV and oxidized collagen IV involves a large number of intracellular components, one of which is NHE. It is well known that NHE is commonly linked to cytoskeleton, thus participating in signal transduction pathways [37,54,55]. Our results showed that inhibition of NHE caused a significant attenuation of 17b-estradiol ability to enhance hemocyte adhesion to ECM proteins, a fact that could lead to the suggestion that NHE could be an important regulator of cell adhesion.…”
Section: Hemocyte Adhesion To Ecm Proteins In 17b-estradiol-treated Hsupporting
confidence: 56%
See 1 more Smart Citation
“…Our results also indicate that the mechanism of 17b-estradiol-induced adhesion to laminin-1, collagen IV and oxidized collagen IV involves a large number of intracellular components, one of which is NHE. It is well known that NHE is commonly linked to cytoskeleton, thus participating in signal transduction pathways [37,54,55]. Our results showed that inhibition of NHE caused a significant attenuation of 17b-estradiol ability to enhance hemocyte adhesion to ECM proteins, a fact that could lead to the suggestion that NHE could be an important regulator of cell adhesion.…”
Section: Hemocyte Adhesion To Ecm Proteins In 17b-estradiol-treated Hsupporting
confidence: 56%
“…Previous studies from our laboratory have shown that cAMP is involved in signaling pathways mediating oxidative responses induced by heavy metals in M. galloprovincialis hemocytes [55]. In addition, other studies suggest that low cytosolic cAMP inhibits phagocytosis in the bivalves Biomphalaria glabarata [86], Crassostrea gigas [87] as well as substratum adhesion of Mytilus californianus hemocytes [88].…”
Section: Alpha2 Integrin Subunit Involvement In 17b-estradiol-treatedmentioning
confidence: 91%
“…Second, based on previous studies, we postulated that the effects observed in OGD would be mediated by ONOO Ϫ ; however, we cannot discount the contribution of other sources of oxidative and nitrosative stress on vascular reactivity, tone, and structure. Also, it is possible that the irreversible reduction in actin cytoskeleton polymerization observed in OGD-treated vessels results in oxidative stress-mediated glutathionylation of actin cysteinyl residues or protein aggregation due to carbonylation and may not be the result of protein nitration, as previous hypothesized (Johansson and Lundberg, 2007;Dailianis et al, 2009). Finally, the results obtained in vessels from diabetic animals cannot be explained solely by the effects of oxidative stress generated during hypoxic conditions.…”
Section: Cerebrovascular Reactivity and Oxidative Stress In Diabetes 411mentioning
confidence: 81%
“…In fact, in the strongly reducing intracellular environment, protein cysteines, mainly in reduced state, are susceptible to oxidation and the concomitant transient formation of intramolecular or intermolecular disulfides with GSH (Ghezzi, 2005;McDonagh and Sheehan, 2007). Similarly, Dailianis et al (2009) reported the formation of reversible mixed disulfides between GSH and cysteine in haemocytes of mussels faced with pro-oxidants after 6 days of exposure, possibly to mask sulfhydryl groups until oxidative stress is overcome. According to the latter, the significant depletion of both PSH and GSH in gills of PAHexposed mussels, as well as the significant correlation obtained among the aforementioned parameters, reveals that thiol modifications due to protein misfolding and disulfide bond formation could be associated with PAH-mediated oxidative stress, thus providing a valuable tool in understanding the cellular redox status.…”
Section: Evaluation Of Pah-mediated Oxidative Stress Via Estimation mentioning
confidence: 98%